International Journal Reputation Enhancement Training: Effectiveness And Implications Analysis Case Study At Higher Education Institutions In Indonesia, Somaliland, and Syria - Mukit, Abdul; Al-Ansi, Abdussalam Hamoud Ghalib; Mulyana, Yana; Zulkiflih, Zulkiflih; Madani, Mohammad Thoyyib; Wahidin, Unang; Hamdy, Mohammad Zainal; Rufaida, Rifki (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The international training program titled